Um middleware declarativo na plataforma Android™ para o sistema brasileiro de televisão digital (SBTVD) - Ferreira, Guilherme Daher (2010)
As with all major digital terrestrial TV systems, the Brazilian middleware called Ginga, supports both declarative applications (through its presentation declarative environment Ginga-NCL) and procedural applications (through its execution procedural environment Ginga-J). Unlike the fixtures, the Brazilian standardization provides that for the portable devices, only the environment Ginga-NCL is required. Today in Brazil there are some portable devices that allow the reception of digital TV signal. However, a minority of these devices are equipped with the middleware adopted by the Brazilian System of Digital Television - SBTVD. Known, although there is no device capable of running applications to digital television, using the Android™ platform operating system, like, there is also no open-source middleware implementation, available to the scientific community, capable of playing, in Brazilian standard, digital TV on portable devices. This paper describes the process used for implementation of Ginga-NCL, as well as details of the encoding for portable devices based on Android™ operating system. As a means to validate the implementation, experiments were conducted to analyze the performance of applications NCL and resource usage of the handheld device.